Cinta Menurut Agustinus Hippo Perspektif Teologis - Wiro, Gregorius (CV. Green Publisher Indonesia, 2025)
The concept of human life, if it is not based on goodness, there will be disputes. A paradoxical thing but inseparable from the reality that humans often experience disputes and peace. However, life is dynamic, every person wants to create a good even though it is not spared from perfection. Effort is proof that the process is something extraordinary so that the expected goals can be achieved. Likewise with human life, the process experienced to find one's identity is a process. The process is combined with the deepest sincerity so that wisdom flows continuously so that it gives aesthetics and color to life. Beauty and color will be remembered by everyone. That is the potential of the person that is created when relying on the creator. The existence between the created and the creator is believed to have a close relationship when reflected through the deepest heart. Both of them revealed to the world that rely on love in every person so that every reality taken is able to save. It is never too late to have a sincere intention. Because sincerity is made when accompanied by a sincere heart, hope is not in vain. Allah is merciful in giving his love to man. Man is God's hope in continuing that love so that it will not be lost. But hope is not lost so that God's love is increasingly present in the world and in the hearts of men.